A SURVEY OF VOCABULARY LEARNING STRATEGY USED BY FIRST-YEAR STUDENTS OF ENGLISH DEPARTMENT OF UNIVERSITAS RIAU - Pratiwi, Kharisma; Jismulatif, Jismulatif; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted in order to investigate what kind of vocabulary learning strategy used by the students in English department of Universitas Riau. In conducting the research, the researcher distributed questionnaire to the first-year students of English Department of Universitas Riau as the sample. 119 students employed in this study were given the questionnaire with seven main domains used in Letchumanan (2016). This research design used quantitative survey research through questionnaires. There were 30 items in the questionnaire. The data were collected by using offline and online submission. The offline submission were collected through the chairman of each class and the online submission were collected through Google Form. The collected data were analyzed by using Microsoft excel. The findings of this study revealed that the student tent to use Cognitive Strategy and Determination Strategy. This result showed that 84,87% first-year student of English Department of Universitas Riau had different ways to learn vocabulary.Key Words: Vocabulary, Vocabulary Learning Strategies, English Study Program